Раскрой скобки и у выражение:
−6(3−b)+3(−2b−2)−6(−9+b)

jumaev1998 jumaev1998    2   25.03.2020 17:55    0

Ответы
dashapeit12 dashapeit12  12.10.2020 04:33

39 - 6b

Пошаговое объяснение:

−6 * (3 − b) + 3 * (−2b − 2) − 6 * (−9 + b) = -6 * 3 - 6 * (-b) + 3 * (-2b) + 3 * (-2) - 6 * (-9) - 6 * b = -18 + 6b - 6b - 6 + 63 - 6b = -18 - 6 + 63 + 6b - 6b - 6b = 39 - 6b

ПОКАЗАТЬ ОТВЕТЫ
chernecov1977 chernecov1977  12.10.2020 04:33
Решение в приложении
Раскрой скобки и у выражение: −6(3−b)+3(−2b−2)−6(−9+b)
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика